2014
DOI: 10.1089/end.2014.0035
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Use and Complications Following Upper Pole Access for Percutaneous Nephrolithotomy

Abstract: Patients undergoing PCNL through UPA had a higher ultimate stone-free rate compared with LPA, while postoperative analgesic requirements and overall complication rates were similar between access sites. A trend toward higher thoracic complication rates was observed in the UPA group, although this did not reach statistical significance. Surgeons should not hesitate to utilize UPA when indicated for patients with large or complex stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
2
1
1
Order By: Relevance
“…Young age and male sex are associated with higher narcotic use postoperatively; however, we did not find such a relationship in our study [11]. Contrary to others, we found that upper pole access in the model strengthened its predictive value (adjusted R 2 ) [12]. Interestingly, BMI had a significant negative impact on VAS assessed 1 and 2 h postoperatively, but there was no correlation in VAS assessed after 2 h. Our assumption is that patients with greater BMI have more fat tissue around the tract, which limits the spread of hematoma around the kidney after PCNL.…”
Section: Discussioncontrasting
confidence: 99%
“…Young age and male sex are associated with higher narcotic use postoperatively; however, we did not find such a relationship in our study [11]. Contrary to others, we found that upper pole access in the model strengthened its predictive value (adjusted R 2 ) [12]. Interestingly, BMI had a significant negative impact on VAS assessed 1 and 2 h postoperatively, but there was no correlation in VAS assessed after 2 h. Our assumption is that patients with greater BMI have more fat tissue around the tract, which limits the spread of hematoma around the kidney after PCNL.…”
Section: Discussioncontrasting
confidence: 99%
“…In this systematic study, based on the performed searches, 17 276 articles were identified, and 324 (1.88%) articles were entered into the final list after conclusive investigation and evaluation according to the checklist [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Это и повреждение плевральной полости, и развитие кровотечения, и большее угловое отклонение тубусом при работе в ЧЛС, которое, растягивая ткань почки, может привести к множеству серьезных осложнений [17,18]. Помимо этого, при высоком, межреберном доступе увеличивается и болевой симптом в послеоперационном периоде в сравнении с доступами через среднюю или нижнюю группу чашечек [19]. Несмотря на трудности и риски, часто верхняя локализация доступа бы-вает необходима для конкретного клинического случая.…”
Section: результатыunclassified